PENGARUH KUALITAS PRODUK DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE PADA MAHASISWA JURUSAN PIPS FKIP UNIVERSITAS RIAU - Sitompul, Cindy Alfanny; Suarman, Suarman; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Absract :This study aims to determine the effect of product quality and brand image on iphone smartphone purchasing decisions on students majoring in PIPS FKIP Riau University. The population and sample in this study were students majoring in PIPS FKIP Riau University who used iPhone smartphones as many as 51 students, while collecting data was done by distributing questionnaires to respondents. This study uses a quantitative method with a descriptive approach. The results showed that the variables of product quality and brand image had a positive and significant effect on purchasing decisions on iPhone smartphones for students majoringin PIPS FKIP Riau University. Based on the results of the R2 test, information was obtained that the R2 value was 0.554 or 55.4%. This means that the percentage of influence given by the independent variable (Product Quality and Brand Image) on the dependent variable (Purchase Decision) is 55.4%. While the remaining 44.6% is influenced by other variables not examined in this study.KeyWords:Quality Product, Brand Image, Purchasing.